Thermal protective ability of electrochemically deposited nickel and nickel – boron coatings - Perevoznikov, Sergey S.; Makovskaya, Ekaterina V.; Tsybulskaya, Ludmila S.; Shendyukov, Vladislav S. (Journal of the Belarusian State University. Chemistry, 2022)
The thermal protective ability of electrochemically deposited Ni and Ni – B coatings was investigated with the aim of their potential application in the production of lamella-type under-die coolers. It has been established that all studied nickelbased coatings retain thermal stability when heated in an air atmosphere in the temperature range from 500 to 700 °C. At a higher annealing temperature (800 °C), the coatings are oxidised (to the greatest extent the nickel coating) with the formation of an oxide layer up to 7–8 μm thick, the main product of oxidation is Ni0.8Cu0.2O. It is shown that the Ni – B coating with a boron content of 4.5 at. % exhibits the highest thermal stability due to the formation of a film of nickel borate (Ni3(BO3)2) on its surface during annealing. A thin continuous film of borate prevents the contact of atmospheric oxygen with the surface and, accordingly, the formation of mixed oxides of copper and nickel, which are a consequence of the thermal instability of nickel coatings during annealing.